Impact of Delirium on Outcomes After Intracerebral Hemorrhage. Issue 2 (February 2022) - Reznik, Michael E.; Margolis, Seth A.; Mahta, Ali; Wendell, Linda C.; Thompson, Bradford B.; Stretz, Christoph; Rudolph, James L.; Boukrina, Olga; Barrett, A.M.; Daiello, Lori A.; Jones, Richard N.; Furie, Karen L.
Abstract : Background and Purpose: Delirium portends worse outcomes after intracerebral hemorrhage (ICH), but it is unclear if symptom resolution or postacute care intensity may mitigate its impact. We aimed to explore differences in outcome associated with delirium resolution before hospital discharge, as well as the potential mediating role of postacute discharge site. Methods: We performed a single-center cohort study on consecutive ICH patients over 2 years. Delirium was diagnosed according to DSM-5 criteria and further classified as persistent or resolved based on delirium status at hospital discharge. We determined the impact of delirium on unfavorable 3-month outcome (modified Rankin Scale score, 4–6) using logistic regression models adjusted for established ICH predictors, then used mediation analysis to examine the indirect effect of delirium via postacute discharge site. Results: Of 590 patients (mean age 70.5±15.5 years, 52% male, 83% White), 59% (n=348) developed delirium during hospitalization. Older age and higher ICH severity were delirium risk factors, but only younger age predicted delirium resolution, which occurred in 75% (161/215) of ICH survivors who had delirium. Delirium was strongly associated with unfavorable outcome, but patients with persistent delirium fared worse (adjusted odds ratio [OR], 7.3 [95% CI, 3.3–16.3]) than those whose delirium resolved (adjusted OR, 3.1 [95% CI, 1.8–5.5]). Patients with delirium were less likely to be discharged to inpatient rehabilitation than skilled nursing facilities (adjusted OR, 0.31 [95% CI, 0.17–0.59]), and postacute care site partially mediated the relationship between delirium and functional outcome in ICH survivors, leading to a 25% reduction in the effect of delirium (without mediator: adjusted OR, 3.0 [95% CI, 1.7–5.6]; with mediator: adjusted OR, 2.3 [95% CI, 1.2–4.3]). Conclusions: Acute delirium resolves in most patients with ICH by hospital discharge, which was associated with better outcomes than in patients with persistent delirium. The impact of delirium on outcomes may be further mitigated by postacute rehabilitation. Abstract : Supplemental Digital Content is available in the text.